Where Justice lives: courthouse architecture and its relationship with surrounding society - del Prado Abizanda, Laia (Revista de derecho aragonés, 2025)
Often overlooked, the design of judicial spaces is of great importance as it locates the judicial process within physical space. Thus, this exploratory research seeks to analyse how courts reflect the sociopolitical and legal reality of the society in which they are framed; to examine the impact of different conceptions of justice on the judicial setting; and to study the relationship between the physical elements of the administration of justice and the legal principles that inspire the judicial process. To this end, a historical overview of the various designs of judicial settings is provided, showing how they have evolved in line with socio-political and legal changes. Likewise, the paper analyses the way in which the physical elements of courts are used to convey principles related to justice as an ideal and specific legal principles. In addition, attention is paid to new trends in judicial architecture. Finally, a case study focused on the Ciudad de la Justicia de Zaragoza is developed through observation and four semi-structured interviews.
Keywords: Courthouse Architecture; History of courts; Architectural trends in courtrooms; Sociology of law